2009
DOI: 10.3109/10408440903384717
|View full text |Cite
|
Sign up to set email alerts
|

Guidance for the classification of carcinogens under the Globally Harmonised System of Classification and Labelling of Chemicals (GHS)

Abstract: The United Nations Conference on Environment and Development (UNCED) has developed criteria for a globally harmonised system of classification and labelling of chemicals (GHS). With regard to carcinogenicity, GHS distinguishes between Category 1 ('known or presumed human carcinogens') and Category 2 ('suspected human carcinogens'). Category 1 carcinogens are divided into Category 1A ('known to have carcinogenic potential for humans'), based largely on human evidence, and 1B ('presumed to have carcinogenic pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 154 publications
0
11
0
Order By: Relevance
“…Regarding data from experimental animals, the information on nasal carcinogenesis in rats after inhalation (McGregor et al 2010) showed that the tumour incidence was slightly elevated at an exposure level of 6 ppm formaldehyde and clearly elevated at 10 ppm and above, whereas at 0.7 and 2 ppm no additional nasal tumours occurred. Thus, there is a non-linear dose-response relationship.…”
Section: Dose-response Relationship Of the Carcinogenicity Of Formaldmentioning
confidence: 99%
“…Regarding data from experimental animals, the information on nasal carcinogenesis in rats after inhalation (McGregor et al 2010) showed that the tumour incidence was slightly elevated at an exposure level of 6 ppm formaldehyde and clearly elevated at 10 ppm and above, whereas at 0.7 and 2 ppm no additional nasal tumours occurred. Thus, there is a non-linear dose-response relationship.…”
Section: Dose-response Relationship Of the Carcinogenicity Of Formaldmentioning
confidence: 99%
“…The UN-GHS, and therefore, the EU CLP approach are based on UN harmonised criteria for weighing the evidence from rodent studies. Regulatory (European Chemicals Agency 2015) and non-regulatory (McGregor et al 2010) guidance is available for weighing the evidence in line with the UN-GHS criteria. Table 7 summarises the assessment of the different UN-GHS Weight of Evidence elements in the EU assessment, and includes a comparison with the weight provided in the IARC evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…In order to start this effort, it is mandatory to find an agreement on the type and quality of data to be used. Papers by Sonich-Mullin et al [ 72 ] or McGregor et al [ 73 ] made attempts defined a number of such criteria for experimental studies to be suitable for risk assessment of possible chemical carcinogens. In most cases such data are used instead of cancer data from human epidemiology.…”
Section: Risk Assessment: Stepwise Approaching the ‘True Risk’mentioning
confidence: 99%